Culinary civilization: the representation of food culture in Ford Madox Ford, Gertrude Stein and Virginia Woolf - O'Brien, N (2017)
This thesis addresses the literary representation of food in the period from 1900 through 1945 in the work of Ford Madox Ford, Gertrude Stein and Virginia Woolf. Taking up nineteenth-century fascinations with sensual and aesthetic taste, these authors explore the implications of food preparation and consumption in Britain, America and France. They use representations of everyday culinary practices as a way to examine articulations of anxiety about the state of civilization, a fear that is amplified and altered by both World Wars. The thesis approaches the question of the significance of food to literary modernism in two ways. The first is a theoretical analysis of modernist ways of thinking about the dialectic between the concepts of civilization and barbarism. The second is grounded in material history, establishing the contexts and conditions of food culture in the first half of the twentieth century. Drawing on sociological thinking from Norbert Elias's conception of the civilizing process and Pierre Bourdieu’s theory of distinction, and using a combined methodology of close reading, biographical and historical analysis, I show that food acts as a lens for these authors' ideas about civil society and modernity. My original contribution to knowledge is threefold. The first is my interpretation of 'culinary Impressionism' as an extension and repositioning of current scholarly thinking about Ford’s literary Impressionism. The second is my reading of Stein's and Toklas's jointly-authored cookbook draft as evidence of their collaboration. This forms the crux of my argument about Stein adapting domestic culinary techniques into her other writing. The third is in my chapter on Virginia Woolf. My original archival research shows that in A Room of One’s Own Woolf’s representation of the financial and culinary difference between men’s and women's dining in colleges at the University of Cambridge is justified and the material inequality was in fact worse than previously understood. I argue that the disparity in institutional food intensifies Woolf’s later reimagining of the term ‘civilization’ in Three Guineas. While drawing on the work of modernist studies scholars on modernism and the everyday, civilization, and food, my project is unique in demonstrating that food reflects modernist conceptions of civilization and barbarism. My thesis contributes to the understanding of transatlantic aesthetics and gendered productions of modernism by illuminating the centrality of agriculture, cookery, domestic work and institutional dining to modernist authors.